Pengaruh Produk Domestik Bruto dan Ekspor Terhadap Foreign Direct Investment di Indonesia, Thailand, dan Vietnam - Yeremia Sahat Kirana (Jurnal Ekonomi Aktual, 2022)
This study analyzes the effect of Gross Domestic Product (GDP) and exports on Foreign Direct Investment (FDI) in Indonesia, Thailand, and Vietnam. This study uses panel data analysis by combining data from time series (2006-2020) and cross-section data (three countries). Data was obtained from the publication of the Central Bureau of Statistics and the World Bank. The results show that GDP and exports positively and significantly affect FDI in Indonesia, Thailand, and Vietnam.